T-bet controls severity of hypersensitivity pneumonitis - Nance Stephanie C; Desai Meena; Abdelsamed Hossam; Fitzpatrick Elizabeth A (BMC, 2011)
Abstract Hypersensitivity Pneumonitis (HP) is an interstitial lung disease that develops following repeated exposure to inhaled environmental antigens. The disease is characterized by alveolitis, granuloma formation and in some patients' fibrosis. IFNγ plays a critical role in HP; in the absence of IFNγ granuloma formation does not occur. However, recent studies using animal models of HP have suggested that HP is a Th17 disease calling into question the role of IFNγ. In this study, we report that initially IFNγ production is dependent on IL-18 and the transcription factor T-bet, however as the disease continues IFNγ production is IL-18-independent and partially T-bet dependent. Although IFNγ production is required for granuloma formation its role is distinct from that of T-bet. Mice that are deficient in T-bet and exposed to S. rectivirgula develop more severe disease characterized by an exacerbated Th17 cell response, decreased Th1 cell response, and increased collagen production in the lung. T-bet-mediated protection does not appear to be due to the development of a protective Th1 response; shifting the balance from a Th17 predominant response to a Th1 response by inhibition of IL-6 also results in lung pathology. The results from this study suggest that both Th1 and Th17 cells can be pathogenic in this model and that IFNγ and T-bet play divergent roles in the disease process.